Morphological Adaptation of Anglicisms in Swedish - Antunović, Goranka (1991)
The article describes the morphological adaptation of English loanwords in Swedish, following the methodology developed by R. Filipović. It presents the results of an analysis of nouns, verbs, adjectives, adverbs and first / last compound elements included in a corpus of 1540 direct loans and hybrids. A detailed presentation is offered of word formation and the morphological adaptation with regard to the following categories: gender and number (declension) for nouns, tense (conjugation) for verbs, gender and comparison for adjectives, adverbial suffixes, formation of preposition and first / last elements of compound words.
Knjiga je objavljen abez ISBN broja. (admin.)
ENG